Serum and blister fluid pharmacokinetics and bactericidal activities of ampicillin-sulbactam, cefotetan, cefoxitin, ceftizoxime, and ticarcillin-clavulanate. - Jaresko, G S (1992)
Ampicillin-sulbactam, ticarcillin-clavulanate, cefoxitin, cefotetan, and ceftizoxime are promoted for the treatment of mixed aerobic-anaerobic bacterial infections. Their activities have been compared in vitro but not in vivo. In order to assess the in vivo activities of these agents in serum and interstitial fluid, we administered single, intravenous doses of these antimicrobial agents to healthy subjects. Concentrations of the antimicrobial agents in serum and suction-induced blister fluid and bactericidal activity were measured by high-pressure liquid chromatography and the standard methodology of the National Committee for Clinical Laboratory Standards, respectively. The organisms used for bactericidal activity tests were one isolate each of Staphylococcus aureus, Klebsiella pneumoniae, and Bacteroides fragilis. Pharmacokinetic parameters in serum and blister fluid were similar to those derived in other investigations. Of note were the high and prolonged concentrations of ticarcillin and cefotetan in blister fluid, despite high-level serum protein binding. The bactericidal activities in serum and blister fluid reflected the relative in vitro activities and kinetic dispositions of the various antimicrobial agents except for the bactericidal activity of cefotetan, which was substantially lower in blister fluid than serum, despite a blister fluid:serum area under the concentration-time curve ratio of 1.5. Similarly, the activity of ticarcillin-clavulanate in blister fluid was also substantially less than would have been predicted by the blister fluid:serum ratio of the area under the concentration-time curve of 1.1, possibly because of the low concentrations of clavulanate in blister fluid. The rankings of the in vivo bactericidal activities of the five drugs were as follows: for S. aureus, ampicillin-sulbactam > ticarcillin-clavulanate > ceftizoxime > cefoxitin > cefotetan; for K. pneumoniae, ceftizoxime > cefotetan > ampicillin-sulbactam = ticarcillin-clavulanate > cefoxitin; and for B.fragilis, ticarcillin-clavulanate > cefotetan > ceftizoxime > ampicillin-sulbactam = cefoxitin.